An investigation of unsteady flow reversal of natural convection in vertical parallel plates by the modified local one-dimensional inviscid relations method. (July 2015) - Fu, Wu-Shung; Huang, Shang-Hao; Li, Chung-Gang
Abstract: An unsteady flow reversal of natural convection in vertical parallel plates with an asymmetrically heated wall is investigated numerically. For clarifying the occurrence of flow reversal, the width of the plates is regarded as a variable, and the non-reflecting boundary condition is adopted at apertures. The methods of the Roe scheme, preconditioning and dual time stepping matching LUSGS are simultaneously used to solve governing equations which are available for a low speed compressible flow problem. The flow reversal is observed under broad width situations and absent under narrow width situations. Distributions of the pressure differences at the apertures are revealed to indicate the occurrence of flow reversal. The present Nusselt numbers, which mean time and area-averaged ones, display relatively good agreement with those of the existing works.